Distinct subpopulations of DN1 thymocytes exhibit preferential γδ T lineage potential - Oh, Seungyoul; Liu, Xin; Tomei, Sara; Luo, Mengxiao; Skinner, Jarrod P.; Berzins, Stuart P.; Naik, Shalin H.; Gray, Daniel H. D.; Chong, Mark M. W. (Frontiers in Immunology, 2023)
The alphabeta and gammadelta T cell lineages both differentiate in the thymus from common uncommitted progenitors. The earliest stage of T cell development is known as CD4-CD8- double negative 1 (DN1), which have previously been shown to be a heterogenous mixture of cells. Of these, only the CD117+ fraction has been proposed to be true T cell progenitors that progress to the DN2 and DN3 thymocyte stages, at which point the development of the alphabeta and gammadelta T cell lineages diverge. However, recently, it has been shown that at least some gammadelta T cells may be derived from a subset of CD117- DN thymocytes. Along with other ambiguities, this suggests that T cell development may not be as straightforward as previously thought. To better understand early T cell development, particularly the heterogeneity of DN1 thymocytes, we performed single cell RNA sequence (scRNAseq) of mouse DN and gammadelta thymocytes and show that the various DN stages are indeed comprised of transcriptionally diverse subpopulations of cells. We also show that multiple subpopulations of DN1 thymocytes exhibit preferential development towards the gammadelta lineage. Furthermore, specific gammadelta-primed DN1 subpopulations preferentially develop into IL-17 or IFNgamma-producing gammadelta T cells. We show that DN1 subpopulations that only give rise to IL-17-producing gammadelta T cells already express many of the transcription factors associated with type 17 immune cell responses, while the DN1 subpopulations that can give rise to IFNgamma-producing gammadelta T cell already express transcription factors associated with type 1 immune cell responses.